Efektivitas Media Filter Pasir Silika dan Arang Ampas Tebu untuk Menurunkan Warna Menggunakan Filtrasi Upflow - Farras Fadillah, Raihan; Badriani, Ririn Endah; Fildzah, Cantika Almas (Rekayasa, 2025)
The availability of quality water is crucial for human survival. This study aims to evaluate the efficiency of reducing water colour through the upflow filtration method with variations in silica sand filter media and bagasse charcoal. The research method involves the preparation of research tools and materials, the manufacture of bagasse charcoal, and filter reactors. Experimental stages include raw water preparation and testing, the filtration process, filtration result water collection and testing, and data analysis. The results showed that the colour removal efficiency at 16.72 TCU was highest in reactor 2 (77.07%) and lowest in reactor 3 (45.85%). At 34.28 TCU, the highest efficiency was in reactor 2 (63.24%) and the lowest in reactor 3 (29.09%). The level of 46.08 TCU showed the highest efficiency in reactor 2 (59.33%) and the lowest in reactor 3 (22.53%). Two Ways ANOVA analysis showed that the thickness of bagasse charcoal filter media has a significant effect on colour reduction because the p value is smaller than 0.05. While the thickness of silica sand has no significant effect because the p value is greater than 0.05, The limitation of colour removal is due to the small surface area of silica sand, which cannot absorb a limited amount of dye.